2014
DOI: 10.3390/ijms150814026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Synthetic Oligopeptide Derived from Enamel Matrix Derivative on Cell Proliferation and Osteoblastic Differentiation of Human Mesenchymal Stem Cells

Abstract: Enamel matrix derivative (EMD) is widely used in periodontal tissue regeneration therapy. However, because the bioactivity of EMD varies from batch to batch, and the use of a synthetic peptide could avoid use from an animal source, a completely synthetic peptide (SP) containing the active component of EMD would be useful. In this study an oligopeptide synthesized derived from EMD was evaluated for whether it contributes to periodontal tissue regeneration. We investigated the effects of the SP on cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 46 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…In this study, we found that SP promoted the activity of ALP and the production of OCN. This result is similar to the effect of EMD and SP in human MSCs [13] and PDL stem cells [14]. Thus, we concluded that SP can also induce differentiation of DPSCs.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In this study, we found that SP promoted the activity of ALP and the production of OCN. This result is similar to the effect of EMD and SP in human MSCs [13] and PDL stem cells [14]. Thus, we concluded that SP can also induce differentiation of DPSCs.…”
Section: Discussionsupporting
confidence: 85%
“…As well known, amelogenin can activate physiological actions through various signaling pathways. In our previous study, SP promotes the cell proliferation via the ERK pathway in human MSCs [13]. Therefore, we believe that SP promotes the cell proliferation via MAPK, such as ERK signaling.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations